“Black People Like Me”: A virtual conference series to engage underserved patients with asthma in patient centered outcomes research - Graham, LeRoy; Hart, Mary; Stinson, Michael; Moise, Rhoda; Mitchell, Lynda; Winders, Tonya A.; Gardner, Donna D. (Research involvement and engagement, 2023)
Background In response to racial inequity in asthma, asthma-related research among diverse patients is vital. However, people from historically marginalized groups are underrepresented in clinical and patient-centered outcomes research (PCOR). The “Black People Like Me” (BPLM) virtual conference series was developed to: (1) engage Black patients with asthma and their caregivers in education and discussions about asthma, and (2) encourage involvement in PCOR. Education about COVID-19 and COVID-19 vaccination was also incorporated. Methods The Project Advisory Group consisting of Black patients, clergy, physicians, and a program evaluator met monthly to develop BPLM. The program consisted of free one-hour virtual sessions held monthly for 6 months. BPLM was promoted through the Allergy & Asthma Network website, emails, social media, and personal contacts with a recruitment goal of ≥ 100 Black patients with asthma or caregivers. Program evaluations, interactive polling questions during each session, and participant pre- and post-session tests were conducted. Results Sessions averaged 658 participants including Black patients, family members, caregivers, Black clergy, health care providers, and other concerned community. Overall, 77% of participants strongly agreed with satisfaction with the sessions. Pre- and post-tests demonstrated that participants exhibited growth in knowledge regarding asthma risk, PCOR, and PCOR research opportunities for patients, exhibited preexisting and sustained knowledge regarding COVID-19 vaccination and side effects, and demonstrated an increased sense of empowerment during healthcare visits. Conclusions BPLM demonstrated that a virtual platform can successfully engage Black communities. Incorporating clergy and religious organizations was critical in developing the trust of the Black community towards BPLM. Plain English summary There are more Black people with asthma in the US than White people. Black people have more hospital stays or deaths from asthma than White people. This highlights the need for Black people to be involved in research. Black people are missing from research. Patient centered outcomes research (PCOR) looks at patient treatment results. A webinar series titled “Black People Like Me” (BPLM) was developed for the Black community. This was a discussion about asthma, COVID-19, and PCOR between patients and experts. BPLM was a free, one-hour, virtual meeting held once a month for 6 months. BPLM was developed by Black patients, clergy, physicians, and a program evaluator. The goal was to meet the needs of the Black community. An average of 658 people participated in each virtual meeting. BPLM found that 77% of attendees were highly satisfied with the sessions. BPLM increased attendee knowledge of asthma, COVID-19, and PCOR. Attendees reported an increased willingness to be involved in PCOR. Including Black clergy helped BPLM be successful by encouraging trust in the program within the Black community. Future programs like BPLM may be developed to help people make decisions about being involved in their health care and PCOR.